Linking Degree of Deacetylation to Coagulation Efficiency of Crustacean Waste Chitosan in Water Treatment - Sinardi Sinardi; Ismail Marzuki; Asriadi Asriadi; Andi Sry Iryani; Faisal Riza Basalamah; Andi Irsyam Mansyur; Hardimas Prayudi (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2026)
Turbidity removal remains challenging because stable colloids resist sedimentation, motivating the use of biodegradable coagulants such as chitosan derived from crustacean waste. However, an integrated quantitative linkage between the degree of deacetylation (DD), zeta potential evolution, and dose-dependent turbidity removal across pH is still limited for shell waste-derived chitosan. This study aimed to relate DD to the zeta potential behavior and coagulation efficiency of chitosan derived from green mussel, crab, and shrimp shells at pH 5, 7, and 9. At pH 7, shrimp-shell chitosan (DD 89.05%) achieved 98.38% turbidity removal at 190 mg/L, crab-shell chitosan (DD 87.64%) achieved 96.72% at 320 mg/L, and green mussel chitosan (DD 77.80%) achieved 95.08% at 300 mg/L [mean±SD, n=3].  The zeta potential shifted from −0.81 mV (untreated synthetic water) to +1.43 to +2.80 mV after dosing, indicating dominant charge neutralization with partial overcompensation. Overall, DD provides a practical screening descriptor for selecting locally sourced chitosan and optimizing the dose for sustainable turbidity control. Valorizing shell waste into effective coagulants may reduce the reliance on inorganic coagulants and support environmentally responsible water treatment practices. This study established an integrated DD zeta potential dose relationship across pH to explain and compare the coagulation performance of locally sourced shell-waste chitosan for turbidity removal.